Decent work, green jobs and the sustainable economy: solutions for climate change and sustainable development - Poschen, Peter (Geneva, 2015)
"Decent Work, Green Jobs and the Sustainable Economy demonstrates that green jobs can be a key economic driver, as the world steps into the largely uncharted territory of building a sustainable and low-carbon global economy. Poschen shows that positive outcomes are possible, but require a clear understanding of the opportunities and challenges.